RIS-assisted wireless communications: prototype validation and measurement progress - YANG Chenhong; SANG Jian; LI Xiao; TANG Wankai; JIN Shi (Dianxin kexue)
In recent years, reconfigurable intelligent surface (RIS) is regarded as one of the promising technologies for 6G because of low power consumption, low cost and the ability to improve communication transmission rate. The progress in measurements for RIS-assisted wireless communication systems was reviewed, with the time-domain and frequency-domain measurement systems introduced. The prototype verification for large-scale fading models, small-scale fading models and channel reciprocity were summarized. Then, the advancements in measuring RIS hardware was reviewed, characteristics were concluded in power consumption, bit levels, polarization, and active RIS. Furthermore, the measurement on RIS coverage enhancement were summarized, introducing the impact of deployment locations, phase design, and effective rank on performance of coverage enhancement. Finally, future research directions and potential challenges faced by practical RIS measurements were discussed.